PERKEMBANGAN PENELITIAN FRAUD DI KALANGAN MAHASISWA: Fraud, Prevention, Detection, Investigation - Fitri Nurlaela (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2023)
Various efforts to minimize fraud have been made by various parties, both from practitioners and academics. Academics produce various kinds of research on fraud starting from the prevention, detection, and investigation stages. This research is a systematic review in the form of a literature review with a statistical descriptive method using 59 data from 2001-2022 research results conducted by Bachelor (S1), Master (S2), and Doctoral (S3) students of State Universities (PTN) throughout West Java. The results showed that fraud prevention research was more conducted by S1 students, and researchers related to non-behavior including internal control systems and anti-fraud strategies with research case studies in the State-Owned Enterprises (BUMN) sector and the government sector. Fraud detection research is mostly carried out by S1 students, researchers associate behavior including skepticism, and professionalism of internal audits with research case studies in the government sector. More fraud investigation research is conducted by S3, researchers relate behavior including competence, commitment, and role of internal audit with research case studies in the government sector.